Validity of CT Scan Measurements of Thoracic and Lumbar Pedicle Dimensions. Issue 1 (April 2016) - Apostolou, Thomas; Chatziprodromidou, Ioanna; Magras, Ioannis; Foroglou, Nikos
Introduction: The transverse and sagittal inner and outer pedicle diameter of thoracic and lumbar vertebrae were measured with an electronic caliper and with CT scan. To determine the validity of CT scan measurements, comparing with those taken by an electronic caliper. Material and Methods: A total of 12 anatomic skeletal specimens were acquired from T1 to L5 in the mean age of 69.6 years. Each vertebral pedicle was measured with an electronic caliper and CT scan. A total of 1632 measurements of 408 pedicles were taken. The data were collected and analyzed using the t -test. The comparison of the measurements between left and right pedicle, males and females, as well as between electronic caliper and CT scan was evaluated. Results: The sagittal diameter of the pedicle was always bigger than 7mm. In the mid-thoracic area (T3-T8), the transverse outer diameter could be less than 4mm, so there is need of use of pediatric screws (<4mm). In the opposite, caudally of T11, the transverse outer diameter was at least 7mm. Conclusion: Significant statistically difference was found between the two genders, while pedicles from male spines were bigger. Additionally, the CT scan was proved to be precise and valid for the measurement of the transverse outer diameter of the pedicle. For this reason, this method becomes valuable for the preoperative evaluation of the pedicle dimension, especially in scoliosis surgery, helping the surgeon to choose the appropriate size of the screws.